Tren Prevalensi dan YLD Stroke di Indonesia Tahun 2021-2023: Analisis Data Global Gurden of Disease - Yuni Asnaini; Titik Kuntari; Vita Widyasari (Universitas Muhammadiyah Manado, 2026)
Stroke remains one of the leading causes of mortality and disability worldwide, including in Indonesia. The increasing prevalence of stroke and Years Lived with Disability (YLD) reflects its growing health burden. This study aimed to analyze trends in stroke prevalence and YLD in Indonesia during 2021–2023 using data from the Global Burden of Disease (GBD). A quantitative descriptive design with an ecological and time-trend approach was employed. Secondary data were obtained from the GBD Results Tool and analyzed using R version 4.4.1. The analysis focused on major geographical regions across Indonesia. The results showed a gradual increase in both stroke prevalence and YLD during the study period. Java recorded the highest prevalence and YLD, while Maluku and Papua showed lower prevalence but greater variation in YLD. These trends were associated with urbanization, unhealthy lifestyles, hypertension, diabetes, and unequal access to healthcare and rehabilitation services. Pearson correlation analysis demonstrated a very strong association between stroke prevalence and YLD (r > 0.99) across all years. The findings highlight increasing stroke burden and regional disparities, emphasizing the need for equitable healthcare access, risk factor control, and strengthened post-stroke rehabilitation programs.